Influence of male targeted short message service on uptake of family planning among spouses in Marsabit County, Kenya - Matoke, Vincent O.; Gitonga, Eliphas M.; Owaka, Isaac O.; Okari, Geoffrey M.; Mutabazi, Michel (International Journal Of Community Medicine And Public Health, 2024)
Background: Family planning helps in regulating the number of children and determine healthy spacing and timing of births between pregnancies. The global contraceptive prevalence stands at 49.0%, Sub-Saharan Africa at 29.0%, Kenya at 56.9% while in Marsabit County at 5.6%. Male spouse involvement on matters of family planning deserves attention. This study aimed at establishing the influence of male targeted short message service on uptake of family planning among female spouses in Marsabit County, Kenya. Methods: A pre-test and post-test quasi experimental study design was adopted involving randomly selected 220 couples from Laisamis and Moyale sub-counties. Intervention of male targeted short message service was offered to male spouses from Moyale sub-county for a period of 4 months. A questionnaire was used to collect data. Quantitative data analysis was done using SPSS. All the required ethical and logistical considerations followed. Results: At baseline level of uptake was overall 14.3%, control 13.2% and intervention 15.4% while at endline overall 30.2%, control 20.4% and intervention 39.5%. Further results revealed that uptake of family planning was increased by use of short message service. Conclusions: The study concluded that the level of uptake was low but with SMS intervention uptake significantly increased. The Ministry of Health should consider integrating male targeted short message service intervention in provision of family planning services to increase uptake.